Peran Teknologi Pendidikan dalam Pembelajaran - Niar Agustian; Unik Hanifah Salsabila (ISLAMIKA, 2021)
The development of information technology which is increasingly rapid in the current era of globalization cannot be avoided anymore its impact on the world of education. Global demands require the world of education to always adjust technological developments to efforts to improve the quality of education, especially adjusting the use of information and communication technology for education, especially in the learning process. This research is a library research method. Educational technology is the application of scientific knowledge to learning, as a result of which learning objectives can be achieved effectively and efficiently, which are not only limited to tools and goods or hardware but also software, and brainware. In the development and utilization of learning technology there are still three basic principles, namely: 1) System approach, 2) Learner centered, 3) Utilization of learning resources as much as possible (utilizing learning resources). The results of the study illustrate that educational technology has a very crucial role in learning. So it can be said that the discovery of educational technology education is a unity that cannot be separated.